Introducing a new standardized nanomaterial environmental toxicity screening testing procedure, ISO/TS 20787: aquatic toxicity assessment of manufactured nanomaterials in saltwater Lakes using Artemia sp. nauplii. (12th February 2019) - Johari, Seyed Ali; Rasmussen, Kirsten; Gulumian, Mary; Ghazi-Khansari, Mahmoud; Tetarazako, Norihisa; Kashiwada, Shosaku; Asghari, Saba; Park, June-Woo; Yu, Il Je
Abstract: This paper introduces a new standardized testing procedure for nanomaterial environmental toxicity (International Organization for Standardization/Technical Specification (ISO/TS) 20787): 'aquatic toxicity assessment of manufactured nanomaterials in saltwater lakes using Artemia sp. Nauplii' intended to generate more reliable and repeatable aquatic toxicity data testing manufactured nanomaterials, using Artemia sp ., to evaluate their possible ecotoxicity in saltwater lake ecosystems. The principles behind testing with Artemia sp . are reviewed and the paper gives an overview of research published between 2009 and 2018 in which manufactured nanomaterials were tested using Artemia sp .